Quality of Life in Cancer Patients Undergoing Radiation Therapy in Karbala - hussein, Mortadha handhal; Ali Kareem Al-Juboori (Universitas Muhammadiyah Sidoarjo, 2025)
Radiation therapy, a cornerstone of cancer treatment, is associated with various physical and psychological side effects that can significantly impair a patient's quality of life (QOL). This study aimed to assess the impact of anxiety and depression on the quality of life of cancer patients undergoing radiotherapy. A prospective descriptive quantitative study was conducted on a non-probability convenience sample of 81 patients at the Center of Oncology and Blood Diseases in Karbala City. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) was used to measure quality of life. The Wilcoxon Signed-Ranks Test was applied to examine differences in QOL. The study found that anxiety and depression levels significantly and negatively impacted the overall quality of life of patients during radiotherapy (p < 0.05). Furthermore, a significant statistical difference was observed in the QOL levels with regard to tumor metastasis (p < 0.05), with patients experiencing metastasis reporting lower QOL. The findings indicate that radiation therapy and its associated psychological distress, particularly in the presence of tumor metastasis, are significant determinants of reduced quality of life in cancer patients. These results underscore the importance of integrating psychological and social support into clinical oncology care to improve patient well-being. Highlights: Anxiety and depression significantly impair quality of life during radiotherapy. Metastatic tumors are linked to lower quality of life. Sociodemographic factors show minimal influence compared to clinical and psychological factors.